THE EVIDENCE OF BACILLIFORM VIRUS A CAUSATIVE AGENT OF WHITE SPOT SYNDROME OF WHITE SHRIMP Penaeus merguiensis - Hari Suprapto (The East Java Biological Society, 2003)
The rod-shape virus particles were found in the hyperthrophied nucleus and cytoplasm of diseased white shrimp Penaeus merguiensis naturally infected by White spot syndrome (WSBV). In natural infection cumulative mortality of shrimp were very high, 95% of population were dead in 3-7 days, and 5% of shrimp population survived. The disease was outbreak in intensive culture farms used the closed circulation sea water system. Others crustacean such as crabs and bentatos were not infected by WSBV at time of sampling. The virus particle were rod-shape ranging from 78 ± 10 nm in diameter and 280 ± 10 nm in length. The pathogenic bacteria mainly dominated by genus Vibrio sp were isolated from shrimp.